Analisis Learning Cycle 7E Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis dan Self Regulated Learning Ditinjau Berdasarkan AQ - Leni Maulani (Universitas Islam Jember, 2021)
This study seeks to examine the improvement in Problem Solving skills and SRL analysis of class XI students using Learning Cycle 7E (LC 7E) learning based on the Adversity Quotient (AQ). This research employs a Mixed Methods Embedded Design. The participants in this study were class XI MIA Program students at SMA Negeri 4 Garut in the 2018-2019 academic year. Class XI MIA 5 (experiment) and class XI MIA 6 (control) were obtained via Random Sampling Group. Tests of problem-solving ability, SRL questionnaires, AQ questionnaires, observation diaries, and interviews were used to collect data. On the basis of the research findings, it can be concluded that the problem-solving skills of students who received LC 7E instruction on AQ Climber are superior to those of conventional students. In contrast, for SRL AQ learners moving from Camper to Climber who receive LC 7E, learning is superior to conventional, with both interpretations falling within the sufficient category. It was also determined that the majority of student and teacher activities in LC 7E learning had accurate interpretations; however, when viewed from the 7E learning stages, the extend stage had the poorest presentation. In addition, LC 7E learning is effective in enhancing PM skills with a 33% success rate, which is a moderate interpretation. Keywords: Learning Cycle 7E, Problem Solving, Self Regulated Learning, Adversity Quotient